The wheelchair skills test, version 2.4: validity of an algorithm-based questionnaire version - Mountain, Anita D; Kirby, R.Lee; Smith, Cher (Archives of physical medicine and rehabilitation, 2004)
Mountain AD, Kirby RL, Smith C. The Wheelchair Skills Test, version 2.4: validity of an algorithm-based questionnaire version. Arch Phys Med Rehabil 2004;85:416–23. To test the hypothesis that an algorithm-based questionnaire version of the Wheelchair Skills Test (WST) would provide a valid assessment of manual wheelchair skills. Within-participant comparisons. Rehabilitation center in Nova Scotia, Canada. Twenty wheelchair users, 11 with musculoskeletal and 9 with neurologic disorders, with a wide range of wheelchair experience (1wk–20y). Each participant completed the questionnaire (WST-Q) and then the objective skills testing (WST, version 2.4). The WST-Q consisted of 3 components, reported as separate versions: the knowledge version (WST-Q [K]) (structured oral questions only); the visual-aid version (WST-Q [VA]) (visual aids added for 6 of the skills); and the categorical perceived-ability version (WST-Q [PA]). The mean total percentage scores for the WST-Q (K), WST-Q (VA), WST-Q (PA), and WST were 60.5%, 62.2%, 64.0%, and 59.8%, respectively. Only the WST-Q (PA) differed significantly from the WST ( P<.05). Positive correlations existed between the objective WST and the WST-Q (K) ( r=.91), WST-Q (VA) ( r=.91), and WST-Q (PA) ( r=.83). The percentage agreement on the individual skill scores ranged from 55% to 100%. The algorithm-based WST-Q has excellent concurrent validity in comparison with objective testing, when assessing the overall manual wheelchair skill levels of wheelchair users with a wide range of experience. It may be useful as a screening tool or when objective testing is impractical.